Eastern Caribbean Currency Union : Staff Report Following Discussions with Regional Institutions. (IMF Staff Country Reports; Country Report ;, 2003)
This paper reviews the IMF's discussions with Eastern Caribbean Currency Union's (ECCU) regional institutions. Discussions focused on the outlook for 2003 and the policy responses needed to arrest the fiscal deterioration and to achieve consolidation over the medium term. Although the short-term outlook for growth appears weak given the external climate, the region can look toward benefits from deeper regional and global integration over the medium term. The IMF staff has also emphasized that structural reforms are needed to improve efficiency, in advance of new trade arrangements.